Using Zeolite as a Partially Replaced Cement in Construction Materials: A Systematic Review of Properties - Hamad, Alaa M.; Ibraheem, Asmaa T.; Ali, Ahmad S.; Moubarak, Azza H. (Al-Nahrain Journal for Engineering Sciences, 2025)
Concrete is considered the most important and widely used building material in the world of construction and building due to its durability, high efficiency in shaping, and relatively reasonable cost. The main component of concrete is cement, and one of the most important problems related to cement is the environmental problems associated with cement manufacturing, as the cement manufacturing process releases a large amount of carbon dioxide. Despite the essential role of concrete in construction, we cannot ignore its environmental impact. Some claim that exploring alternative materials or innovative building techniques would reduce the carbon footprint and enhance sustainability in the industry. Partial cement replacement with pozzolanic materials like zeolite is a key technique to reduce carbon dioxide emissions. Zeolite, which reduces permeability, is a typical concrete ingredient that strengthens and lasts. Recently, natural zeolite has become a prominent concrete pozzolanic component. For environmental preservation and sustainable development, various experiments were done on concrete with pozzolanic components partially substituting cement and compared to ordinary concrete. A partial replacement of cement with zeolite improves the properties of concrete up to a certain age and mixing ratio. More than 44 relevant articles from 2004–2024 were selected from 762 papers evaluated for this paper. This paper reviews natural zeolite research in real applications. Additionally, it provided a cutting-edge review of natural zeolite literature through a critical analysis of various previous investigations. It also helped to understand how zeolite influences concrete mixture workability, strength, and durability. Since zeolite is a major concrete ingredient, it should be promoted as a sustainable resource.